2022
DOI: 10.1007/s10903-022-01402-z
|View full text |Cite|
|
Sign up to set email alerts
|

Does the Integration of Migrants in the Host Society Raise COVID-19 Vaccine Acceptance? Evidence From a Nationwide Survey in Japan

Abstract: Research indicates that integration contributes to maintaining health among migrants, yet little is known about the association between integration and vaccination acceptance. This study aimed to explore COVID-19 vaccine intention and acceptance, and the association between integration and vaccine hesitancy among migrants in Japan. We conducted an internet survey among migrants in Japan from October 5 to October 14, 2021. Among 1,455 participants, 11.6% reported hesitancy toward COVID-19 vaccination. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…A study among Black African and Caribbean communities in the UK, for example, found that the uncertainty of the pandemic, combined with contemporary and historical mistrust and a lack of identity-aligned messaging, contributed to belief in conspiracy theories and low engagement with COVID-19 health-protective behaviours (18, 29). A study in Japan found that the social integration of migrants positively correlated with their COVID-19 vaccine acceptance, underscoring the importance of inclusion and community engagement (33). Building on this recent work and the different understandings of these concepts, this study aims to explore the contextual factors shaping migrants’ COVID-19 vaccination decision-making through an in-depth study with Congolese migrants in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…A study among Black African and Caribbean communities in the UK, for example, found that the uncertainty of the pandemic, combined with contemporary and historical mistrust and a lack of identity-aligned messaging, contributed to belief in conspiracy theories and low engagement with COVID-19 health-protective behaviours (18, 29). A study in Japan found that the social integration of migrants positively correlated with their COVID-19 vaccine acceptance, underscoring the importance of inclusion and community engagement (33). Building on this recent work and the different understandings of these concepts, this study aims to explore the contextual factors shaping migrants’ COVID-19 vaccination decision-making through an in-depth study with Congolese migrants in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with higher education and good language skills—immigrants with higher levels of integration—were likely to be overrepresented. Because highly integrated immigrants have a higher willingness to receive COVID-19 vaccination, the vaccination acceptance rates among the participants of our survey may be higher than that of the actual immigrant population in Japan [14] . As little information or official statistics on the vaccination status of foreign residents in Japan is available, our study has important evidentiary value with regard to the health disparities between immigrants and the host population in Japan.…”
Section: Discussionmentioning
confidence: 84%
“…We conducted a nationwide Internet survey among foreign national residents of Japan aged 20 years or above (from October 5–14, 2021) and Japanese national residents (from October 26–28, 2021). The COVID-19 vaccination in Japan began in February 2021 and is free for all residents of Japan, including immigrants [14] . During the survey period, infections in Japan were very low; the proportion of the fully vaccinated population was 60.2% on October 5, 2021 [15] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most common sociodemographic factors associated with COVID-19 acceptance were gender, age, level of education, and marital status (Table 4). Female gender (11-21), younger age (14, 15, 17, 22-29), lower level of education (12, 16, 17, 19, 20, 22, 26, 30-32), and being single (11, 13, 26) were associated with lower vaccine acceptance in most studies.…”
Section: Methodsmentioning
confidence: 89%